Hydroxyapatite formation in biomimetic synthesis with the interface of a pDA@SIS membrane. Issue 21 (3rd May 2022) - Zhu, Qiuhong; Jiao, Hua; Zhao, Xiaoliang; Tang, Yufei; Zhao, Kang; Gou, Xingchun
Abstract : Porcine decellularized small intestine submucosa (SIS) is a collagen membrane, which offers great potential as an organic substrate template in mineralization processes due to its good biodegradability and biocompatibility. Abstract : Porcine decellularized small intestine submucosa (SIS) is a collagen membrane, which offers great potential as an organic substrate template in mineralization processes due to its good biodegradability and biocompatibility. However, a long period of mineralization and low efficiency are apparent, and the mechanism of collagen fiber mineralization has often been neglected in the previous literature. Thus, in this paper, we present a novel model of biomimetic collagen mineralization which uses dopamine (DA) molecules with the activating and retouching function of SIS collagen membranes and regulating collagen mineralization to construct the structure of mineralized collagen hard tissues. The crystal biomimetic mineralization growth of calcium phosphate on membranes is studied in different solid–liquid interfaces with a double ion self-assembled diffusion system under the simulated physiological microenvironment. In the system, pDA@SIS membranes are used to control the concentration of Ca 2+ and PO4 3− ionic diffusion to generate supersaturation reaction conditions in 1–14 days. The system can successfully obtain polycrystals with low crystallinity on the pDA-collagen complex template surface of collagen fibers and along the collagen fibers. It initiates a generalized bionic mineralization pathway which can reduce the nucleation interfacial energy to promote rapid hydroxyapatite (HAP) nucleation and crystallization and accelerate the rate of collagen fiber mineralization. The pDA@SIS mineralized collagen membrane shows good biocompatibility with 100% cellular activity in the CCK-8 test, which significantly improved the adhesion proliferation of MC3T3-E1 cells. The pDA-SIS collagen complex, as a new type of mineralization template, may propose a new collagen mineralization strategy to produce a mineralized pDA@SIS scaffold bone-like material for tissue engineering or can potentially be applied in bone repair and regeneration.